The Relationship between Biochemical and Hemoglobin Results and Quality Index Scores of the Mediterranean Diet of Pregnant Women in the First and the Third Trimester - Hürer, Nazife; Yıldız, Emine (Progress in Nutrition, 2022)
Introduction: The mother’s nutrition and life style during gestation is very essential for her own health as well as the infant’s health. The aim of nutrition during gestation is both to keep the balance of nutrient factor spares in her body through meeting the physiological needs and also to provide the necessary energy and nutrient factors for the normal growth of the fetus. Aim: This study was conducted with the purpose of analyzing the relationship between the biochemical and hemoglobin results and the quality index scores of the Mediterranean Diet in pregnants in the first and third trimester as well as comparing the biochemical and hemoglobin results of pregnants in the first and third trimester. Method: Total 30 pregnants participated in the research who were among 20-35 ages and were followed in a private hospital in Nicosia in Turkish Republic of Northern Cyprus. The demographic characteristics, nutrition habits, behavioral changes for nutrients during gestation were questioned and the anthropometric measurements were done. Also, in the first interview and in the III. trimester pre-prandial blood samples were obtained from the pregnants and analyses were done in a medical laboratory in terms of biochemical (Urea, Alanine amino Tranferase (ALT), Aspartate Amino Transferase (AST), pre-prandial blood glucose (PBG), Thyroid Stimulating Hormone (TSH), Creatinine, Free T4, folic acid, vitamin D (vit.), B12 vit.) and hemoglobin analyses were done. The Mediterranean nutrition habit was evaluated by the Mediterranean Diet Quality Index (MDQI). Results: When the Mediterranean Diet Quality Index scores of pregnants in I. and III. trimester are analyzed, the average of the Mediterranean Diet Quality Index of I. and III. trimester were found as x =7.5±1.88, x =8.73±2.08 respectively, and the minimum score was 3, whereas the maximum obtained score was 12. There has not been a statistically meaningful correlation between the biochemical and hemoglobin findings of the pregnants in the  I. trimester and the MDQI scores (p>0.05), whereas there has been a positive way meaningful correlation between the MDQI scores and the AST values measured in the III. trimester (p0.05). In addition; there has been statistically meaningful difference between the values of creatinine, hemoglobin, AST and ALT values measured in the I. trimester and III. trimester (p